Asthma in competitive cross-country skiers: A systematic review and meta-analysis - Mäki-Heikkilä, R.; Karjalainen, J.; Parkkari, J.; Valtonen, M.; Lehtimäki, L. (Sports Medicine, 2020)
Introduction: In cross-country skiing, the repetitive ventilation of large amounts of cold and dry air strains the airways. The aim of this systematic review was to establish an overview of the current literature on asthma in cross-country skiers, biathletes and ski-orienteers. Methods: Six databases were searched on August 29, 2019. The search yielded 2161 articles. Thirty articles fulfilled the search criteria and were pooled together for a qualitative synthesis. Eight articles were included in the meta-analysis on the prevalence of asthma and the use of asthma medication. Results: According to the meta-analysis, the prevalence of self-reported physician-diagnosed asthma in skiers was 21% (95% CI 14-28%). The onset age of asthma was higher in skiers than in non-skiers with asthma. The prevalence of asthma medication use was on average 23% (CI 95% 19-26%). Several studies reported that asthma was underdiagnosed in skiers, as previously healthy skiers without a prior asthma diagnosis or medication use were frequently found to fulfill diagnostic criteria for asthma according to lung function tests. Studies using bronchial biopsy demonstrated that eosinophilic asthma is not detected in skiers with asthma as often as it is in non-skiers with asthma and that there are signs of airway inflammation even in non-asthmatic skiers. Conclusion: Our findings suggest that the accuracy and coverage of diagnosing asthma in skiers has improved over the recent decades. However, the optimal treatment and natural course of asthma in this population remain unclear. Future research should investigate how the intensity of training, airway infections and their treatment affect the development of asthma among skiers.